A clinical and microbiological evaluation of systemic and local metronidazole delivery in early onset periodontitis patients. - (:unkn) unknown (My University, 1996)
The present study describes selected clinical and microbiological results obtained by treatment with local (Elyzol) and systemic (Flagyl) use of metronidazole alone and/or mechanical subgingival debridement in early onset periodontitis (EOP). Twelve patients, with lesions not distributed as in classical localized juvenile periodontitis, were included. They were randomly divided into local and systemic treatment groups each comprising 6 individuals, in each of whom 4 sites (one site/quadrant) with a probing depth of > or = 5 mm were selected and treated with separate treatment modalities. The overall treatment design provided 6 different test groups. Groups of quadrants received 1) scaling and root planing 2) local metronidazole treatment 3) systemic metronidazole treatment 4) local metronidazole combined with scaling and root planing 5) systemic metronidazole combined with scaling and root planing 6) No treatment. The microbiological and clinical effects of treatment modalities were monitored over 42 days. The results demonstrated reductions in mean counts of obligate anaerobic and capnophilic microorganisms coupled with significant improvements in mean clinical measurements (gingivitis, probing depth, attachment level) in all groups, except the untreated. Scaling and root planing provided an initial clinical improvement with a selective reduction of periodontopathogens (92.6% obligate anaerobes, 42.9% capnophilic microorganisms), whereas the combination of local or systemic metronidazole with scaling and root planing were found superior in reducing capnophilic bacteria (93.7% and 93.4%, respectively). It is of critical importance to have a treatment rationale for EOP, since bacterial differences exist in the etiological subforms of periodontitis. Microbial testing may be justified before prescribing the adjunctive antibiotic and selecting the mode of delivery for the successful clinical management of EOP.